Socioeconomic status and livestock scenario of Spiti valley of Western Himalayas - BISHIST, ROHIT; WANGMO, DEACHEN; GAUTAM, KRISHAN LAL; S, KHALANDAR (The Indian Journal of Animal Sciences, 2022)
Livestock rearing plays a cogent role in the economy of Himachal Pradesh, as it contributes about 28-30% of the total value of agricultural produce. In the study area, the majority of livestock farmers belonged to marginal category and were rearing sheep, goat, local cattle, Churu and Yak for their sustenance. The literacy rate in the area was highest in semi-medium farmers followed by small and marginal farmers. Study revealed that contribution of livestock sector to the gross farmer’s income was highest in case of marginal farmers. In the study area, inadequate exposure to improved breeding practices, scarcity of green fodder and poor marketing facilities were the major constraints in livestock production. The majority of farmers in this region were adopting modern veterinary medicines/vaccines for the treatment of their livestock; however, ethnoveterinary practices are still in progress. In the light of results obtained, it can be concluded that the socio-economic status of the livestock farmers in the alpine area of Lahaul and Spiti is appreciable, though there are multiple constraints in livestock production practices which directly affect the animal health and thus the farmers livelihood.